Effect of Low-Frequency Repetitive Transcranial Magnetic Stimulation on Executive Function and Its Neural Mechanism: An Event-Related Potential Study - Liu, Sishi; Wang, Xianglong; Ma, Junqin; Wang, Kangling; Wang, Zhengtao; Li, Jie; Chen, Jiali; Zhan, Hongrui; Wu, Wen (Frontiers in Neuroscience, 2021)
Objective: Executive function refers to the conscious control of thinking and behavior in psychological process. Executive dysfunction widely exists in a variety of neuropsychiatric diseases, and is closely related to the decline of daily living ability and function. This study intends to explore the effect of low-frequency repetitive transcranial magnetic stimulation（rTMS） on executive function and its neural mechanism by using Event related potential(ERP) , so as to provide basis for further study on the relationship between cerebral cortex and executive function. Method: Task switching paradigm was used to study the cognitive flexibility in executive function. Thirty one healthy subjects were randomly assigned to receive rTMS stimulation (1Hz rTMS or sham rTMS) to the left dorsolateral prefrontal cortex（DLPFC） twice. After each stimulation,They underwent ERP recordings while performing switching task procedure immediately. Result: ERP analysis showed that there is a significant switching effect in frontal and central scalp locations, and the amplitude of P2 in switch trials was greater than that in non-switch trials. In the frontal scalp locations, the N2 amplitude in switch trials is more negative than that in non-switch trials in sham stimulation, but there was no significant difference in rTMS stimulation. In central and parietal channels, there was significant rTMS stimulation effect on P3 and LPC component. The amplitude of rTMS stimulation was smaller than that of sham stimulation. Conclusion: Low frequency rTMS of the left DLPFC can cause decline of executive function, resulting in the change of N2 effect and the decrease of P3,LPC component during task switching, which is of positive significance for the evaluation and treatment of executive function.